A Study on the Relationship between Family Shareholding and Company’s Operating Performance - Evidences from a Small Open Economy - Li, Jian-Fa; Chang, Ni-Chen; Li, Katherine A. (Journal of Ecohumanism, 2024)
Our study is to investigate how the ownership structure and financial aspects of family-controlled firms influence their operating performance. The interests of major shareholders are aligned, this could positively impact the company’s operating performance. Conversely, dominant shareholders might entrench themselves in a way that doesn’t necessarily benefit the operating performance. The presence of a second largest shareholder acts as a check and balance on the first largest shareholder. We reveal an inverted U-shaped relationship between the shareholding ratio of foreign institutional investors (SRFII) and operating performance. It suggests that as SRFII increases, operating performance initially improves but might decline after reaching a certain threshold. This finding highlights the importance of maintaining balance in SRFII to ensure alignment of interests between company leadership and the company’s overall goals. Excessive foreign ownership could potentially lead to divergent interests that may not be aligned with the company’s best interests. We also find that higher equity pledge ratio among key leadership roles might adversely affect operating performance. Pledged shares could restrict decision-making flexibility and potentially lead to conflicts of interest. These findings shed light on the complex dynamics within family-controlled firms, particularly how ownership structure and financial arrangements could influence operational outcomes.